Anti-aliasing method for second-order curves on a hexagonal raster - Melnyk, Oleksandr; Prysiazhniuk, Tetiana (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2026)
This paper presents a method for anti-aliasing of second-order curves using method of additional lines. The proposed method refers to supersampling methods, which allow achieving a high level of smoothing even for complex contours. For each type of second-order curves, the method is implemented using an evaluation function. The algorithm by which the method is implemented consists of six main sides. Direct formation of the internal and external additional lines of pixels is implemented in the fourth block of the algorithm. The pixels of both the internal and external additional lines are painted with a colour intensity of 50% of the colour intensity of the pixels of the main contour of the curve. This creates the appearance of a smooth transition and smoothes the steps. This allows reducing the aliasing effect on the boundaries of graphic objects of high curvature. The method significantly increases the speed of anti-aliasing implementation, due to the possibility of using it when constructing the main contour of the curve on a hexagonal raster. The method of additional lines for anti-aliasing of second-order curves on a hexagonal raster is equally effective for all types of second-order curves.